Analisis Keefektifan Ekoenzim sebagai Pembersih Kandang Ayam dari Limbah Buah Jeruk (Citrus sp.) - A. Mahdia; P. A. Safitri; R. F. Setiarini; V. F. A. Maherani; M. N. Ahsani; M. S. Soenarno (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Sanitation of the cage usually requires a sanitizer containing a powerful cleaning fluid to sterilize the cage. Materials commonly used for cage sanitation are detergent or disinfectants used to eradicate pathogenic microorganisms that cause bacteria, fungi, or other microorganisms. Eco enzyme is an alternative natural cleaning agent derived from fresh fruit waste through fermentation. This study aimed to make eco enzymes for cleaning chicken coops from citrus waste, characterize the microbiological eco enzymes, and test the effectiveness of eco enzymes as chicken coop cleaners. Eco enzymes from fresh citrus waste after a 3-month fermentation period contained bacteria and fungi of 1.9 x 106CFU/ml and 8.5 x 105CFU/ml, respectively, with a pH of 3.39±0.023. The eco enzyme of cage cleaning fluid from citrus waste (Citrus sp.) can inhibit the growth of Escherichia coli and Staphylococcus aureus through confrontation tests in the laboratory. Testing the effectiveness of eco enzymes in chicken coops can reduce the number of bacteria five times more than detergents for the same area.